Effects of selective MMP‐13 inhibition in squamous cell carcinoma depend on estrogen. Issue 12 (7th August 2014) - Meides, Alice; Gutschalk, Claudia M.; Devel, Laurent; Beau, Fabrice; Czarny, Bertrand; Hensler, Sabine; Neugebauer, Julia; Dive, Vincent; Angel, Peter; Mueller, Margareta M.
<x xml:space="preserve">Abstract</x> Matrix metalloproteinases like MMP‐13 cleave and remodel the extracellular matrix and thereby play a crucial role in tumor progression in vivo. Using a highly selective inhibitor to block MMP‐13 protein activity, we demonstrate a striking inhibitory effect on invasive tumor growth and vascularization in murine skin squamous cell carcinoma (SCC). Therapy outcome critically depends on animal age in C57Bl/6 mice and was successful in old female but not in young female mice. Treatment success was recovered by ovariectomy in young and abolished by 17ß‐estradiol supplementation in old mice, suggesting a hormone dependent inhibitor effect. Responsiveness of the tumorigenic keratinocytes BDVII and fibroblasts to 17ß‐estradiol was confirmed in vitro, where MMP‐13 inhibitor treatment led to a reduction of cell invasion and vascular endothelial growth factor (VEGF) release. This correlated well with a less invasive and vascularized tumor in treated mice in vivo. 17ß‐estradiol supplementation also reduced invasion and VEGF release in vitro with no additional reduction on MMP‐13 inhibitor treatment. This suggests that low 17ß‐estradiol levels in old mice in vivo lead to enhanced MMP‐13 levels and VEGF release, allowing a more effective inhibitor treatment compared to young mice. In our study, we present a strong link between lower estrogen levels in old female mice, an elevated MMP‐13 level, which results in a more effective MMP‐13 inhibitor treatment in fibroblasts and SCC cells in vitro and in vivo.